Modeling Competing Line-broadening Mechanisms in Neutron Star Atmospheres: Interference between Motional Stark and Ion Broadening - Thomas A. Gomez; Mark C. Zammit; Igor Bray; Christopher J. Fontes; Jackson R. White; Harold Johnson (The Astrophysical Journal, 2024)
Neutron star surfaces have extremely high magnetic fields. In the atmosphere, the broadening of spectral lines will be substantial from the dense plasma as well as from the magnetic field. One broadening mechanism of note is due to the motional Stark effect (MSE)—an additional electric field that arises from the motion of the atom in the magnetic field. However, approximate formulae are often used to construct atmosphere models, and the MSE is assumed to be the dominant line-broadening mechanism even in ions. Detailed pressure-broadening models in these extreme magnetic fields are now currently being developed. In these more detailed models, it was suggested that the MSE may not be as large as previously predicted. If correct, this hypothesis implies that neutron star line widths might be dominated by pressure broadening rather than by motional Stark broadening. We find that, in the absence of plasma perturbations, for typical magnetic fields ( B = 10 ^12 G), mid- Z elements, such as oxygen, have motional Stark widths of order 1 eV for transitions between dipole-allowed transitions from the ground state, though higher temperatures and transitions to higher-energy states are expected to have more broadening. The MSE also breaks down selection rules, giving rise to forbidden transitions, which have much larger widths. When plasma perturbations are included, we find that the plasma perturbation and motional Stark processes are not independent and, as a result, the spectral lines become narrow in a nontrivial way and display harmonics of the ion cyclotron frequency.